2001
DOI: 10.1081/lpr-100103170
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes Containing Dopamine Entrapped in Response to Transmembrane Ammonium Sulfate Gradient as Carrier System for Dopamine Delivery Into the Brain of Parkinsonian Mice

Abstract: The active loading of liposomes with dopamine in response to an ammonium sulfate gradient was studied. This method can be regarded as a mean to more efficiently improve the liposomal dopamine/lipids ratio in comparison to conventional methods of liposome preparation. Trapping efficiency of dopamine into liposomes exhibiting a transmembrane ammonium sulfate gradient was shown to be dependent on liposome lipid composition, lipid concentration and temperature. Dopamine-containing liposomes with alpha-tocopherol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This could be ascribed to their small inner volume and drug leakage from small and intermediate-sized unilamellar vesicles (up to 100 nm) , Uchegbu & Vyas, 1998Zhigaltsev et al, 2001). A reduction in vesicle size may be achieved by a number of methods:…”
Section: Niosome Size's Influence On In Vivo Performancementioning
confidence: 99%
“…This could be ascribed to their small inner volume and drug leakage from small and intermediate-sized unilamellar vesicles (up to 100 nm) , Uchegbu & Vyas, 1998Zhigaltsev et al, 2001). A reduction in vesicle size may be achieved by a number of methods:…”
Section: Niosome Size's Influence On In Vivo Performancementioning
confidence: 99%
“…Long circulating liposomal daunorubicin plus tamoxifen was prepared using an ammonium sulfate gradient loading method as reported previously. 22,23 In detail, EPC, PEG2000-DSPE (55/40/ 5, mmol/mmol) and an appropriate tamoxifen (drug/liposome materials, 5 mg/75 mg) were dissolved in chloroform containing 20% methanol in a pear-shaped ask. The organic solvents were removed by evaporation with a rotary vacuum evaporator.…”
Section: Preparation Of the Long Circulating Liposomesmentioning
confidence: 99%
“…A total nasal dose (100 Bl) was administered in small volumes over 30 min. It has been shown that animals can be protected from lesions induced by this neurotoxin by treating them with acidic fibroblast growth factor (aFGF) and basic fibroblast growth factor (bFGF), which are present in the dopaminergic neurons [106]. Drug levels were assessed in blood and in the CSF, collected by cisternal puncture.…”
Section: Nasal Administration Of High Molecular Weight Drugsmentioning
confidence: 99%